2007
DOI: 10.1590/s0043-31442007000300016
|View full text |Cite
|
Sign up to set email alerts
|

The mean levels of adherence and factors contributing to non-adherence in patients on Highly Active Antiretroviral Therapy

Abstract: Objective:To determine the mean level of adherence and factors contributing to non-adherence in patients on Highly Active Antiretroviral Therapy (HAART). Methods: An observational study was done on 101 HIV/AIDS patients attending the Centre for HIV/ AIDS Research, Education and Services (CHARES) -University Hospital of the West Indies, between May 2006 and August 2006. A questionnaire was administered asking questions re: prescribed and actual dosing frequency and number of antiretroviral tablets for the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Several recent studies have reported average adherence rates to ART up to 80% to 90% of prescribed doses (Etard et al, 2007;Vriesendorp et al, 2007;Williams, Clarke, Williams, & Barton, 2007) as compared with the average of 50% to other chronic medication (Altice & Friedland, 1998;Stone, 2001). The current study reported that pill count was the most commonly used method to measure treatment adherence.…”
Section: Challenges In Treatment Follow-upmentioning
confidence: 66%
“…Several recent studies have reported average adherence rates to ART up to 80% to 90% of prescribed doses (Etard et al, 2007;Vriesendorp et al, 2007;Williams, Clarke, Williams, & Barton, 2007) as compared with the average of 50% to other chronic medication (Altice & Friedland, 1998;Stone, 2001). The current study reported that pill count was the most commonly used method to measure treatment adherence.…”
Section: Challenges In Treatment Follow-upmentioning
confidence: 66%
“…It is well known that adherence to therapies is poor in generally nonsymptomatic conditions, such as hypertension (33%-84% nonadherence; Conlin et al, 2001) and type 2 diabetes (36%-87% nonadherence; Lee et al, 2006). Moreover, patient adherence is often low even in lifethreatening conditions such as cancer (20%-100% nonadherence to oral treatments; Partridge et al, 2002) and HIV/AIDS (70%-80% nonadherence to highly active antiretroviral therapy; Williams et al, 2007).…”
Section: Adherence In Chronic Illnessesmentioning
confidence: 99%
“…For example in "silent" disorders such as hypertension adherence is reported to be only between 16% and 66% (Conlin, Gerth, Fox, Roehm, & Boccuzzi, 2001); even in symptomatic and life-threatening conditions such as cancer and HIV, treatment adherence is reported to be equally low in some cases (e.g., as low as 20% to oral neoplastic agents) (Partridge, Avorn, Wang, & Winer, 2002;Williams, Clarke, Williams, & Barton, 2007).…”
mentioning
confidence: 99%